Physiological indicators of students training in of special medical group with the disease of vegetative-vascular dystonia of mixed type. - Mordvinova А.V; Burla О.М (Kharkov National Pedagogical University, 2011)
The analysis of physiological indicators of students training in special medical group. Showed the level of somatic health, adaptive capacity of the cardiovascular system and physiological indicators of the first-year students. Proved that the level of physical training of students each year decreases. In experiment took part 21 students of first year study.